1999
DOI: 10.1097/00000539-199908000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Propofol Versus Propofol-Ketamine Sedation for Retrobulbar Nerve Block

Abstract: Anesthesiologists frequently perform retrobulbar blocks while simultaneously providing sedation. Using ketamine to supplement propofol sedation provided a faster onset and improved the quality of sedation during the retrobulbar block procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 12 publications
2
12
0
Order By: Relevance
“…[37] The incidence and mean duration of apnea in the present study were higher in the propofol group than in the ketofol group. Consistent with our results, previous studies[161833] concluded that the addition of ketamine to propofol is associated with less prolonged apnea and less risk of respiratory depression compared with propofol alone. Also low-dose ketamine added to propofol sedation attenuated propofol-induced hypoventilation and preserved response to carbon dioxide.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…[37] The incidence and mean duration of apnea in the present study were higher in the propofol group than in the ketofol group. Consistent with our results, previous studies[161833] concluded that the addition of ketamine to propofol is associated with less prolonged apnea and less risk of respiratory depression compared with propofol alone. Also low-dose ketamine added to propofol sedation attenuated propofol-induced hypoventilation and preserved response to carbon dioxide.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our results, Frey and colleagues[18] stated that ketofol was associated with shorter time until sedation compared to propofol. Induction time (time to reach BIS of 40) was faster in the ketofol group (150 ± 23.5 seconds) than in the propofol group (205 ± 37.4 seconds).…”
Section: Discussionsupporting
confidence: 92%
“…Various sedative and analgesic drug regimens prior to the placement of local anaesthesia for cataract surgery have been investigated [12, 13, 14, 15, 16]. The ideal drug should render the patient pain free and immobile during the placement of peribulbar block and surgery and should be free of side-effects.…”
Section: Discussionmentioning
confidence: 99%
“…Many single- and multiple-drug regimens have been investigated for use prior to the placement of ophthalmic nerve blocks [12, 13, 14, 15, 16]. But new intravenous regimens continue to be evaluated because so far, none resolved all problems such as airway obstruction, over-sedation and respiratory or cardiovascular depression.…”
Section: Introductionmentioning
confidence: 99%
“…Monitored anesthesia care (MAC) is performed without regional anesthesia to improve the patient's postoperative condition in vascular procedures. The most commonly used agents for MAC are midazolam, propofol, and fentanyl [1,2,3]. It is well known that a combination of these drugs is often difficult to titrate and may induce respiratory depression.…”
Section: Introductionmentioning
confidence: 99%